Mechanics of humanoid robot. (16th November 2020) - Hashimoto, Kenji
Abstract : The effects of mechanical system dynamics are often disregarded in the design process of humanoid robots. Sophisticated control methods may compensate for some limitations of the mechanical structure, however, principal limitations of the system performance can arise from poor mechanical architecture. Therefore, it is important to develop robot hardware that behaves close to an ideal model and that is easy to be modeled from the viewpoint of mechanics. This paper surveys the mechanics of humanoid robots from the viewpoint of joint mechanism, kinematic structure of the leg joints, and foot mechanisms. Firstly, the actuators and power transmission mechanisms for driving the joints are summarized. For the kinematic structure of leg joints, the characteristics of serial and parallel mechanisms are explained, and the specific configuration of the hip, knee and ankle joints are introduced. In order to make a robot move as close to the ideal movement as possible, we need to design the robot to reduce backlash at each joint. Various foot mechanisms are also introduced in the paper. GRAPHICAL ABSTRACT: UF0001